Unraveling usnic acid: a comparison of biosynthetic gene clusters between two reindeer lichen (Cladonia rangiferina and C. uncialis). Issue 11 (November 2022) - Egbert, Susan; Hoffman, Jordan R.; McMullin, R. Troy; Lendemer, James C.; Sorensen, John L.
Abstract: Lichenized fungi are known for their production of a diversity of secondary metabolites, many of which have broad biological and pharmacological applications. By far the most well-studied of these metabolites is usnic acid. While this metabolite has been well-known and researched for decades, the gene cluster responsible for its production was only recently identified from the species Cladonia uncialis . Usnic acid production varies considerably in the genus Cladonia, even among closely related taxa, and many species, such as C. rangiferina, have been inferred to be incapable of producing the metabolite based on analysis by thin-layer chromatography (TLC). We sequenced and examined the usnic acid biosynthetic gene clusters, or lack thereof, from four closely related Cladonia species ( C. oricola, C. rangiferina, C. stygia, and C. subtenuis ), and compare them against those of C. uncialis . We complement this comparison with tiered chemical profile analyses to confirm the presence or absence of usnic acid in select samples, using both HPLC and LC-MS. Despite long-standing reporting that C. rangiferina lacks the ability to produce usnic acid, we observed functional gene clusters from the species and detected usnic acid when extracts were examined by LC-MS. By contrast, C. stygia and C. oricola, have been previously described as lacking the ability to produce usnic acid, lacked the gene cluster entirely, and no usnic acid could be detected in C. oricola extracts via HPLC or LC-MS. This work suggests that chemical profiles attained through inexpensive and low-sensitivity methods like TLC may fail to detect low abundance metabolites that can be taxonomically informative. This study also bolsters understanding of the usnic acid gene cluster in lichens, revealing differences among domains of the polyketide synthase which may explain observed differences in expression. These results reinforce the need for comprehensive characterization of lichen secondary metabolite profiles with sensitive LC-MS methods. Graphical abstract: Image 1 Highlights: Lichen chemotaxonomy historically based on analysis using thin-layer chromatography (TLC). Cladonia rangiferina reported as not producing usnic acid based on TLC. Genome sequencing of C. rangiferina reveals usnic acid gene cluster. Analysis by LC-MS reveals detectable amounts of usnic acid in C. rangiferina. Lichen chemotaxonomy may need to be revisited with more sensitive techniques.